2006
DOI: 10.1111/j.1467-9817.2006.00309.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of prosodic sensitivity in children's reading development

Abstract: While the critical importance of phonological awareness (segmental phonology) to reading ability is well established, the potential role of prosody (suprasegmental phonology) in reading development has only recently been explored. This study examined the relationship between children's prosodic skills and reading ability. Hierarchical multiple regression analyses examined the unique contribution of wordlevel and phrase-level prosodic skills to the prediction of three concurrent measures of reading ability in 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
192
8
20

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(242 citation statements)
references
References 41 publications
18
192
8
20
Order By: Relevance
“…However it is plausible that, prosodic sensitivity might also have a direct role in word reading as stress assignment is necessary for reading aloud multisyllabic words. Certainly there is some empirical evidence for a direct role in word reading as while prosodic sensitivity is associated with vocabulary knowledge and phonological awareness, it can also predict word reading independently of this association (e.g., Holliman et al, 2008;Whalley & Hansen, 2006). Such findings have been replicated more recently (see Calet, Gutiérrez-Palma, Simpson, González-Trujillo, & Defior, 2015) where it was argued that prosodic sensitivity may have a direct effect on word reading.…”
Section: Prosody and Early Literacysupporting
confidence: 60%
See 2 more Smart Citations
“…However it is plausible that, prosodic sensitivity might also have a direct role in word reading as stress assignment is necessary for reading aloud multisyllabic words. Certainly there is some empirical evidence for a direct role in word reading as while prosodic sensitivity is associated with vocabulary knowledge and phonological awareness, it can also predict word reading independently of this association (e.g., Holliman et al, 2008;Whalley & Hansen, 2006). Such findings have been replicated more recently (see Calet, Gutiérrez-Palma, Simpson, González-Trujillo, & Defior, 2015) where it was argued that prosodic sensitivity may have a direct effect on word reading.…”
Section: Prosody and Early Literacysupporting
confidence: 60%
“…Over the last 16 years in particular a literature has been developing that implicates a role for prosody in reading acquisition (e.g., Goswami et al, 2002;Goswami, Gerson & Astruc, 2010;Holliman, Wood, & Sheehy, 2008, 2010a, 2010bLeong, Hämäläinen, Soltész, & Goswami, 2011;Schwanenflugel, Hamilton, Kuhn, Wisenbaker, & Stahl, 2004;Whalley & Hansen, 2006). However, a key challenge remains in understanding the mechanisms by which prosody influences reading (and spelling) and whether it has a direct effect and/or an indirect effect via other mediating variables.…”
Section: Prosody and Early Literacymentioning
confidence: 99%
See 1 more Smart Citation
“…Veenendaal, Groen, and Verhoeven (2014) found that, besides reading aloud prosody, proficiency in speech prosody (as elicited in a story-telling task) had a positive effect on reading comprehension. Whalley and Hansen (2006) demonstrated that children with a poorer performance on accent placement in a reiterative speech task performed poorer on reading comprehension than children with a better prosodic proficiency (see also Holliman, Wood, & Sheehy, 2010a, 2010b. Similarly, prosodic sensitivity appears to be highly predictive of reading proficiency in children with developmental dyslexia (e.g.…”
Section: Focus Structure In Language Processingmentioning
confidence: 99%
“…For example, sensitivity to prosodic patterns in dyslexia can be measured using a reiterant speech task, the "DeeDee" task (Whalley and Hansen 2006). Here each syllable in a word is converted into the same syllable (DEE), removing most phonetic information while retaining the stress and rhythm patterns of the original words and phrases.…”
Section: Speech Rhythm and Syllable Stress Perception In Dyslexiamentioning
confidence: 99%